Synthesis and properties of semicrystalline non‐isocyanate polyurethane with tunable triple shape memory properties. Issue 14 (2nd February 2023) - Yin, Xingshan; Liu, Huameng; Lin, Ruijun; Liu, Xiaochun; Huang, Zhiyi; Du, Jiahao; Gu, Yuxin; Lin, Xiaofeng; Lin, Wenjing; Yi, Guobin
Abstract: Nowadays, polyurethanes with multifunctional and multiple shape memory effects, especially those without the use of toxic phosgene and isocyanate, have attracted significant attention. In this work, to prepare a kind of non‐isocyanate polyurethane (NIPU) with triple shape memory effect, we introduced the behenic acid (BA) with good crystallinity into the NIPUs network, which combines glass transition of the cross‐linked network and crystallization‐melting of behenic acid, endowing the NIPUs with two independent transition temperatures: the glass transition temperature ( T g ) and crystallization melting temperature ( T m ). Specifically, the NIPUs were synthesized by the addition reaction of bi‐functional cyclic carbonate and semi‐crystalline curing agent. The bi‐functional cyclic carbonate was prepared by thiol‐ene click reaction, and the BA was grafted onto polyethyleneimine to prepare semi‐crystalline curing agent. By adjusting the ratio of BA to PEI and curing temperature, the crystallinity of NIPU can be tuned in a wide range, so that the NIPUs has tunable and superior triple shape memory performance, and the shape recovery rate is almost 100%. Abstract :